PENGARUH HEDONIC SHOPPING MOTIVATION DAN FASHION INVOLVEMENT TERHADAP IMPULSIVE BUYING PRODUK FAST FASHION MELALUI POSITIVE EMOTION PADA GENERASI Z PENGGUNA SHOPEE DI JAKARTA - Maria Al Qibthya; Dita Puruwita; Ivan Putranto (STKIP Subang, 2026)
This research investigates the effect of hedonic shopping motivation and fashion involvement on impulsive buying of fast fashion items among Generation Z Shopee users in Jakarta, both directly and through positive emotion as a mediating factor. Applying a quantitative PLS-SEM approach with 154 respondents obtained through purposive sampling, the findings reveal that hedonic shopping motivation and fashion involvement lead to impulsive buying through distinct psychological pathways, with positive emotion functioning as the central mechanism linking both to impulsive buying. These findings broaden the Stimulus-Organism-Response framework and offer practical implications for Shopee and fast fashion sellers in strengthening emotion-based marketing strategies.